2013
DOI: 10.19173/irrodl.v14i4.1454
|View full text |Cite
|
Sign up to set email alerts
|

Virtual worlds: Relationship between real life and experience in Second Life

Abstract: Due to the unique applications of virtual reality in many modern contexts, Second Life in several areas,potentially addressing the future role of educating social work students regarding research methodology in online virtual reality interactions. Implications for social work are discussed including engaging clients using incentives for social participation built into the SL milieu.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…interviews, focus group and content analysis) (e.g. Anstadt et al, 2013;Ali, 2015;Bas al and Kaynak, 2020). The studies using surveys and experiments tend to use structural equations, regression analysis or factorial analysis for data treatment (Fokides, 2017;Silva et al, 2019).…”
Section: Theory: New Research Directionsmentioning
confidence: 99%
“…interviews, focus group and content analysis) (e.g. Anstadt et al, 2013;Ali, 2015;Bas al and Kaynak, 2020). The studies using surveys and experiments tend to use structural equations, regression analysis or factorial analysis for data treatment (Fokides, 2017;Silva et al, 2019).…”
Section: Theory: New Research Directionsmentioning
confidence: 99%
“…However, measures looking at comprehension, connectedness, contingency, and closeness did not show an advantage. Additionally, Anstadt et al (2013) found that SL users believed that avatars closely represented the real people behind them.…”
Section: Avatar-based Counselingmentioning
confidence: 99%
“…Khairuni (2016) said that the negative impact of uncontrolled use of social media was that children were less socialized with direct activities, lazy, addicted to online games, imitating scenes of violence, and pornography. Anstadt et al (2013) emphasized that the development of information and communication technology should be able to be used for positive activities such as the development of knowledge, seeking information and references, becoming a medium for distance education, developing social networks and public services. In addition, Flavián, et al (2016) said that the development of information and communication technology media influences and changes individual and social interactions.…”
Section: Holistic Rehabilitation Model In Nurul Firdaus Boarding Schoolmentioning
confidence: 99%